Cover Feature: In Vivo Applications of Bioorthogonal Reactions: Chemistry and Targeting Mechanisms (Chem. Eur. J. 20/2023). Issue 20 (9th March 2023) - Mitry, Madonna M. A.; Greco, Francesca; Osborn, Helen M. I.
Abstract : Bioorthogonal chemistry refers to reactions that can proceed in biological systems without interfering with biological processes. It has enabled the study of biomolecules in their native environment and has facilitated advanced imaging and diagnostic applications. In their Review (DOI: 10.1002/chem.202203942 ), M. M. A. Mitry, F. Greco and H. M. I. Osborn critically appraise the suitability of bioorthogonal reactions for in vivo applications. Areas of focus are chemical reactions and the targeting mechanisms used to deliver the bioorthogonal reactions' components.